PENGARUH INFLUENCER MARKETING DAN KEPERCAYAAN KONSUMEN TERHADAP MINAT BELI ULANG DI TIKTOK SHOP (STUDI PADA MAHASISWA INSTITUT TEKNOLOGI DAN BISNIS KRISTEN BUKIT PENGHARAPAN) - Yusak Prakoso; Miko Ripaldo (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
This study aims to analyze the influence of Influencer Marketing and Consumer Trust on Repurchase Intention on TikTok Shop, with respondents consisting of students from the Institut Teknologi dan Bisnis Kristen Bukit Pengharapan. This research employs a quantitative approach using multiple linear regression analysis. The results indicate that Influencer Marketing has a positive and significant effect on Repurchase Intention. In addition, Consumer Trust also has a positive and significant effect and is found to be the most dominant factor influencing Repurchase Intention. Influencer Marketing not only directly increases repurchase intention but also plays a role in building consumer trust, which further strengthens the likelihood of repeat purchases. These findings provide important insights for businesses in developing digital marketing strategies, particularly by leveraging influencers to enhance consumer loyalty on social media-based e-commerce platforms such as TikTok Shop.